Progression of basal ganglia pathology in heterozygous Q175 knock‐in Huntington's disease mice. Issue 7 (20th September 2020) - Deng, Yunping; Wang, Hongbing; Joni, Marion; Sekhri, Radhika; Reiner, Anton
Abstract: We used behavioral testing and morphological methods to detail the progression of basal ganglia neuron type‐specific pathology and the deficits stemming from them in male heterozygous Q175 mice, compared to age‐matched WT males. A rotarod deficit was not present in Q175 mice until 18 months, but increased open field turn rate (reflecting hyperkinesia) and open field anxiety were evident at 6 months. No loss of striatal neurons was seen out to 18 months, but ENK+ and DARPP32+ striatal perikarya were fewer by 6 months, due to diminished expression, with further decline by 18 months. No reduction in SP+ striatal perikarya or striatal interneurons was seen in Q175 mice at 18 months, but cholinergic interneurons showed dendrite attenuation by 6 months. Despite reduced ENK expression in indirect pathway striatal perikarya, ENK‐immunostained terminals in globus pallidus externus (GPe) were more abundant at 6 months and remained so out to 18 months. Similarly, SP‐immunostained terminals from striatal direct pathway neurons were more abundant in globus pallidus internus and substantia nigra at 6 months and remained so at 18 months. FoxP2+ arkypallidal GPe neurons and subthalamic nucleus neurons were lost by 18 months but not prototypical PARV+ GPe neurons or dopaminergic nigral neurons. Our results show that striatal projection neuron abnormalities and behavioral abnormalities reflecting them develop between 2 and 6 months of age in Q175 male heterozygotes, indicating early effects of the HD mutation. The striatal pathologies resemble those in human HD, but are less severe at 18 months than even in premanifest HD. Abstract : Striatal cholinergic (ChAT+) interneurons in WT and heterozygous Q175 mice at 18 months of age. The images show that striatal cholinergic interneuron abundance is comparable, but dendrites in Q175 mice are significantly fewer and shorter. These abnormalities and diverse striatal projection neuron abnormalities develop between 2 and 6 months of age in Q175 heterozygotes, indicating early effects of the HD mutation on the striatum in these mice that in many regards resemble those in human HD. Nonetheless, the pathologies do not yet involve overt striatal neuron loss even by 18 months, indicating they are less severe than even in premanifest HD.